2006
DOI: 10.1038/sj.onc.1209396
|View full text |Cite
|
Sign up to set email alerts
|

Expression of inappropriate cadherins by epithelial tumor cells promotes endocytosis and degradation of E-cadherin via competition for p120ctn

Abstract: Cadherin cell-cell adhesion proteins play an important role in modulating the behavior of tumor cells. E-cadherin serves as a suppressor of tumor cell invasion, and when tumor cells turn on the expression of a non-epithelial cadherin, they often express less E-cadherin, enhancing the tumorigenic phenotype of the cells. Here, we show that when A431 cells are forced to express R-cadherin, they dramatically downregulate the expression of endogenous E-and P-cadherin. In addition, we show that this downregulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 51 publications
3
48
0
2
Order By: Relevance
“…Our finding that P-cadherin as a critical mediator of the invasive phenotype further supports the view that the incorrect expression of another adhesion molecule, rather than a decrease in E-cadherin, is associated with an increased invasive potential (Nieman et al, 1999;Feltes et al, 2002;Suyama et al, 2002;Maeda et al, 2006). Unlike E-cadherin, P-cadherin can promote motility and invasion in carcinoma cells.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our finding that P-cadherin as a critical mediator of the invasive phenotype further supports the view that the incorrect expression of another adhesion molecule, rather than a decrease in E-cadherin, is associated with an increased invasive potential (Nieman et al, 1999;Feltes et al, 2002;Suyama et al, 2002;Maeda et al, 2006). Unlike E-cadherin, P-cadherin can promote motility and invasion in carcinoma cells.…”
Section: Discussionsupporting
confidence: 84%
“…Instead, GnRHa stimulated activation of the P-cadherin promoter (Figure 2b; Po0.05), suggesting a transcriptional mechanism of regulation. P-cadherin contributes to the invasive phenotype It has been suggested that expression of an inappropriate cadherin may directly contribute to the invasive phenotype (Nieman et al, 1999;Feltes et al, 2002;Suyama et al, 2002;Maeda et al, 2006). To test whether P-cadherin may promote migration/invasion, we stably transfected Caov-3 and OVCAR-3 cells with P-cadherin and analyzed their effects on cell migration/invasion.…”
Section: Resultsmentioning
confidence: 99%
“…Induction of N-cadherin during EMT has previously been reported in other systems. 16 In addition to E-cadherin, UM-SCC-38 cells express P-cadherin and incorporate this cadherin into adherens junctions in these cells. Unlike E-cadherin, a significant amount of P-cadherin remains in UM-SCC-38/slug cells however the protein is not expressed in a homogeneous manner as was observed in control cells or as N-cadherin is expressed in UM-SCC-38/slug cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The above studies on p120-catenin provide a hint as to why forced expression of an inappropriate cadherin promotes degradation of endogenous cadherins. In A431 cells, forced expression of R-cadherin results in degradation of endogenous Ecadherin and P-cadherin, and the degradation of endogenous cadherins is due to competition for binding to p120-catenin (Maeda et al, 2006). Thus, it is possible for cadherin switching to occur following modulation of transcription of only one cadherin.…”
Section: Post-transcriptional Control Of Cadherin Levelsmentioning
confidence: 99%